Napoleon and Wellington - Roberts, Andrew 1963- (Weidenfeld & Nicolson, 2001)
"At breakfast on the morning of the battle of Waterloo, the Emperor Napoleon declared that the Duke of Wellington was a bad general, the British were bad soldiers and that France could not fail to win an easy victory Forever afterwards, historians have accused him of gross overconfidence and massively underestimating the calibre of the British commander opposed to him Now the award-winning historian Andrew Roberts presents an original, highly revisionist view of the relationship between the two greatest captains of their age."--BOOK JACKET.
Keywords: Napoleon <I, Emperor of the French, 1769-1821>; Napoléon <Ier, empereur des Français , 1769-1821>; Wellington, Arthur Wellesley <duc de, 1769-1852>; Napoleon <I, Emperor of the French, 1769-1821> -- Military leadership; Wellington, Arthur Wellesley <Duke of, 1769-1852> -- Military leadership; Napoleon -- I. -- Frankreich, Kaiser -- 1769-1821; Wellington, Arthur Wellesley of -- 1769-1852; Geschichte; Guerres napoléoniennes (1800-1815) - Campagnes et batailles - Russie; Militaire bevelhebbers; Militaires - Biographies - France; Militaires - Biographies - Grande-Bretagne; Generals -- France -- Biography; Generals -- Great Britain -- Biography; Napoleonic Wars, 1800-1815; Führung; Napoleonische Kriege; Militär; Frankreich; Großbritannien; Biografie